10. PENGARUH KEBERADAAN KOMITE MANAJEMEN RISIKO TERHADAP LUAS PENGUNGKAPAN SUKARELA - Purbawati, Dinalestari (Faculty of Social and Political Sciences Diponegoro University, 2014)
This study consisted of two test models. The first test model investigated the association between board characteristics such as board size, and proportion of non-executive directors, as well as firm characteristics (e.g. organisational complexity, financial reporting risk, and leverage) on the existence of a risk management committee. The second test model investigated the association between the existence of a risk management committee on the extent of voluntary disclosure. This study is explanatory research used secondary data. Data was collected from the annual reports non-financial companies listed on the Indonesian Stock Exchange (BEI) the period 2008, 2009 and 2010. Analysis tools used in the first test model is a logistic regression model and a second test using OLS regression. The results showed that only the variable board size who have a significant positive effect on the existence of the risk management committee and the existence of the risk management committee has a significant positive effect on the extent of voluntary disclosure.